Neural regulation of bone marrow adipose tissue. Issue 4 (July 2021) - Zhang, Xiao; Hassan, Mohamed G.; Scheller, Erica L.
Abstract : Bone marrow adipose tissue (BMAT) is an important cellular component of the skeleton. Understanding how it is regulated by the nervous system is crucial to the study of bone and bone marrow related diseases. BMAT is innervated by sympathetic and sensory axons in bone and fluctuations in local nerve density and function may contribute to its distinct physiologic adaptations at various skeletal sites. BMAT is directly responsive to adrenergic signals. In addition, neural regulation of surrounding cells may modify BMAT-specific responses, providing many potential avenues for both direct and indirect neural regulation of BMAT metabolism. Lastly, BMAT and peripheral adipose tissues share the same autonomic pathways across the central neuraxis and regulation of BMAT may occur in diverse clinical settings of neurologic and metabolic disease. This review will highlight what is known and unknown about the neural regulation of BMAT and discuss opportunities for future research in the field.